Carbohydrate Intake In Amateur Cyclists - Fernandes, Higor José; Nones, Débora Cristina da Cunha; Calazans, Ana Paula Carvalho Thiers (Seven Editora, 2023)
Cycling is a sport and Olympic modality that is widely practiced among individuals, especially among amateur people who seek physical and mental well-being, and an unbalanced diet and inadequate water intake can cause a drop in performance and fatigue in athletes or practitioners of the modality. . Carbohydrate ingestion during prolonged activities, over one hour, improves performance and delays fatigue in sports such as cycling, which involves intermittent high-intensity efforts. Thus, it is necessary to know the consumption of carbohydrates and water of amateur cycling practitioners, as well as to analyze the consumption of dietary supplements in this public, identifying if there is guidance from trained professionals. The present study demonstrated that the participating amateur cyclists know the importance of carbohydrates for improving performance, knowing the necessary amount of carbohydrates per day, however, they do not know how often carbohydrates should be consumed during the pedal. In addition, there are questions about hydration and the use of food supplements. This shows the importance of nutritionist guidance in improving the performance and health of cyclists. DOI: https://doi.org/10.56238/colleinternhealthscienv1-107